(untitled) (International Journal of Environmental Sciences, 2025)
Goods and Services Tax (GST) is a major reform in the indirect tax system in India. It has created a framework where both the Centre and the States work closely for better revenue sharing providing a strong basis for fiscal federalism. Petroleum is a major source of revenue in India and especially the States earn hefty amount through imposition of Sales tax on it. It has been mandated by the Central Goods and Services Tax Act, 2017 that GST would be imposed on petroleum products on notification by the government on the recommendation of the GST Council. But it has not happened yet after a number of years have passed implementing GST. The discontentment between the Centre and the States on that regard gave rise to various issues of concern. This article is an attempt to analyse the different forms of taxes imposed by the Centre and the States on the petroleum products, debates on the floor of the Lok Sabha and the GST Council regarding imposition of GST on such products and reasons for the States’ reluctance in bringing such products under GST and its impact on the economy. The Researcher also proposes a few suggestions for bringing petroleum products under GST structure step by step.